Constante cosmológica: algumas consequências algébricas e dinâmicas - Beltrán Almeida, J. P [UNESP] (2006)
In this thesis we study two diﬀerent aspects of the physics of the cosmological constant: the algebraic structure of the de Sitter group, and its implications in the large scale dynamics of the Universe. In the ﬁrst part we present a general description of the geometrical structure of de Sitter space, and a discussion about the structure of de Sitter group. We review the contraction limits of de Sitter group, obtained by means of the Inönü-Wigner procedure, and we study in detail the formal limit 'lâmbda' 'SETA' 'INFINITO'. In this limit, one obtains a maximally-symmetric, singular spacetime, transitive under proper conformal transformations, and with thermodynamic properties that agreee with the idea of an initial condition for a big-bang Universe. In the same context, we propose a special relativity based on the de Sitter group. In this theory, the cosmological constant introduces an invariant length scale: the de Sitter radius. The introduction of this invariant scale does not imply a violation of the Lorentz symmetry, but simply a change in the causal structure of the spacetime, as well as in the basic notions of momentum and energy. In the second part of the thesis, that related with cosmological applications, a dynamic model for the cosmological constant will be presented. In this model, as a consequence of Einstein's equations, a variation in 'lâmbda' must necessarily be compensated by creation or destruction of matterenergy, in such a way that the total energy remains constant. A particular model allowing for the evolution of the cosmological constant is presented, which is based on the holographic principle. We will show how this model can accommodate simultaneously the accelerated expansion of the Universe and the coincidence in the magnitude of matter and dark energy densities